Effect of pentoxifylline administration on an experimental rat model of intraperitoneal adhesion (Annals of Medical Research, 2021)
Aim: Intraabdominal adhesions are the pathological structures that form between the peritoneal surfaces throughout the healing of the peritoneal surface defects with scar formation. Adhesions are a significant problem because they affect the quality of life, lead to morbidity and mortality, and increase health expenses. We have investigated the effectiveness of pentoxifylline (PTX), which is a methyl xanthine derivative, on the development of experimentally generated intraperitoneal adhesions in rats.Materials and Methods: In our study, 30 Wistar Albino rats, each weighing an average of 200-250 grams, were used. In this study, 3 groups of 10 rats were formed. As the adhesion model, cecotomy method was preferred and applied. Groups were classified as; the sham group, control group and PTX group. In the Sham group, merely laparotomy was applied, the control group was intraperitoneal 5 cc isotonic after the cecotomy, and the PTX group was intraperitoneal 100 mg / kg after the cecotomy. Rats were sacrificed on the 15 th day. Macroscopic, microscopic adhesion and adhesion tissues were evaluated with regard to hydroxyproline levels.Results: In the comparison of the groups from the macroscopic point of view, there was a noteworthy difference in adhesion between the sham group and the PTX group (p = 0.027) and between the control group and the PTX group (p = 0.001).Conclusion: In this study, it was observed that PTX can reduce intraabdominal adhesion and increase the level of hydroxyproline after surgery.
Keywords: Adhesion; abdominal surgery; pentoxifylline